Health conditions of older persons in rural Malaysia - Wan Ahmad, Wan Ibrahim (International digital organization for scientific information (IDOSI), 2014)
Health condition is an important element for the maintenance of human visions, hearing and mobility.The objective of the present paper is to examine the health conditions older people in terms of type of illness, frequency of going to see physician to seek medication, self-health assessments, comparison of health with health status in the past and the comparison of health status of older persons with peers. A total of 214 older populations, from a population aged 60 years and above living in rural areas in the district of Limbongan, Kelantan, Malaysia were selected as respondents.Results of the study show that not many respondents are suffering from chronic illness that requires ongoing medical treatment. There are quite large proportions of older respondents who never come to see physician to get treatment.Only a small number of the respondents are less satisfied with their health condition. Thet majority of respondents perceived their health at the time of the study more or less similar to the previous health status and compare their health condition with their peers, almost half felt their health status is not much different with their peers.The nature of health condition of older people is felt important to understand to help government creating a good action plan to address the needs of older persons.